A Novel Approach for Risk Assessment of Building Damage via Metro Tunnel Construction - Hai-Lin Wang; Yuan Liu; Yuan Jiang; Zhi-Teng Wang (Advances in Civil Engineering)
The impact of shield construction on the surrounding buildings involves numerous factors, and the factors are uncertain and ambiguous, which have a great impact on the progress and safety of the project. Therefore, this paper developed a systematic approach for the risk assessment of existing buildings adjacent to tunneling excavation. Firstly, a risk assessment system for adjacent buildings in shield tunneling environments was proposed. Secondly, the weighting of factors was calculated by Pythagorean fuzzy AHP. Then, the VIKOR method was used to divide the risk of existing buildings adjacent to tunneling excavation into five uneven levels. Finally, the extended VIKOR with interval numbers was first introduced in risk assessment of building adjacent to tunneling environment to determine a specific building risk level. The proposed approach was successfully applied to the risk assessment of several buildings adjacent to tunnel construction of Metro Line 4 of Changsha. The accuracy and effectiveness of the constructed new approach were verified by comparing the obtained evaluation results with the actual situation on-site. This work provides a new method for similar engineering risk assessment.